PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi pada pegawai Bank Rakyat Indonesia Cabang Bangkalan) - Akbar, Zulfikar; Faidal, Faidal (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine leadership and work motivation on employee performance. The method used in this research is population research with a total sample of 38 respondents. The type of data used is in the form of cross-sectional data, namely the type of data obtained by collecting data only during field research. With multiple linear regression analysis method. The results of this study indicate that 1) The results of the study indicate that leadership has a positive and significant influence on the performance of BRI employees. 2) The results showed that motivation had a positive and significant effect on BRI employee performance. 3) The results showed that leadership and motivation variables simultaneously had an effect on employee performance variables